2018
DOI: 10.1177/1179554918782477
|View full text |Cite|
|
Sign up to set email alerts
|

A Single-Centre Experience on the Management of Adenosarcoma: A Successful Report of an Integrated Medical and Surgical Approach

Abstract: Adenosarcomas are the rarest form of uterine sarcomas, and clinical experience with their management is still limited. Here, we reported 7 patients with uterine adenosarcoma referred to our institution, focusing on main pathologic features, their medical history, and long-term follow-up. Among these patients, we provided a detailed description of the medical history of a 49-year-old woman with advanced uterine adenosarcoma with sarcomatous overgrowth who presented a brilliant radiologic and pathologic response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Case reports and case series explore the use of adjuvant HT in UAS although no trials or series of at least 10 patients have been reported in literature[74,75]. Further investigations are required to identify the subset of patients that might obtain a proven benefit from HT in the adjuvant setting.…”
Section: Adjuvant Hormonal Therapymentioning
confidence: 99%
“…Case reports and case series explore the use of adjuvant HT in UAS although no trials or series of at least 10 patients have been reported in literature[74,75]. Further investigations are required to identify the subset of patients that might obtain a proven benefit from HT in the adjuvant setting.…”
Section: Adjuvant Hormonal Therapymentioning
confidence: 99%
“…Some studies have found that adenomyosis and endometriosis may be associated with the occurrence of Müllerian adenosarcoma, and endometriosis bleeding induces persistent oxidative stress and DNA damage, which may be one of the influencing factors of the disease [ 12 , 13 ]. For cervix-derived Müllerian adenosarcoma, differs from most intracervical lesions, although the persistence of HPV is thought to be one of the major risk factors for the development of intracervical lesions and recurrence after treatment [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most characteristic symptom is a recurrent polypoid lesion, which is biopsied on several occasions, in which a definitive diagnosis cannot be reached; A misdiagnosis can even occur, of which the most frequent is a cervical polyp ( 10 ). These tumors can occasionally occur outside the uterus (ovary and fallopian tube) ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous components can be observed in the last cases, especially rhabdomyosarcoma, and this represents a more aggressive clinical course. In one of the longest series published (7 cases), none of the cases with sarcomatous overgrowth presented heterologous areas ( 11 ). Our case presented a heterologous component of grade 2 chondrosarcoma, which is exceptional and has not been previously reported in the literature.…”
Section: Discussionmentioning
confidence: 99%